Risk effects cascade up to an obligate scavenger. Issue 2 (3rd January 2023) - Perrig, Paula L.; Lambertucci, Sergio A.; Donadio, Emiliano; Smith, Justine A.; Middleton, Arthur D.; Pauli, Jonathan N.
Abstract: The effects of predation risk on prey populations have been studied extensively; yet, how risk is manifested in a trophically linked guild—scavengers—has been overlooked. Risk could be particularly consequential for obligate scavengers that are vulnerable while foraging and rely on carrion provisioned by, and shared with, apex predators. We investigated whether Andean condors ( Vultur gryphus ) respond to predation risk in a landscape where the main source of carrion are camelids killed by pumas ( Puma concolor ). We hypothesized that condors would exhibit different behavioral responses to predation risk while they search, encounter, and exploit carrion. We explored condor habitat selection while flying by tracking nine birds with satellite transmitters and monitored via camera traps 41 natural carcasses and 25 experimental carrion stations. We found that condors searched for carrion in areas with a high probability of occurrence of puma kills. However, condors avoided exploiting carrion in areas featuring tall vegetation and steep slopes—selected by pumas to stalk prey—suggesting that condors manage risk primarily through the identification of safe foraging sites prior to landing. Our finding that condors avoided foraging near stalking cover for pumas highlights the importance of risk effects beyond predator–prey interactions, particularly for obligate scavengers.